Gender dynamics in banana seed systems and impact on banana bunchy top disease recovery in Cameroon - Nkengla-Asi, Lilian; Omondi, Aman Bonaventure; Che Simo, Vincent; Assam, Elizabeth; Ngatat, Sergine; Boonabaana, Brenda (SAGE Publications, 2020)
Enhancing opportunities for women and men in banana production is vital for promoting gender equity in sub-Saharan Africa. This study investigated the gendered differences in access to and decision-making over banana production resources and services in banana bunchy top disease affected areas in Cameroon. A mixed methods approach was used, comprising an intra-household survey (n = 109 households). Six sex disaggregated focus group discussions and key informant interviews were organized to collect primary data in three communities in Ambam District in Southern Cameroon. These data were used to compare men and women in resource access and production within households and villages. Men had greater say in decision-making over productive resources and information services even when women were more involved in actual seed and site selection. Planting materials were mainly sourced from old fields although men were more likely to buy banana seeds than women farmers. In practical terms, access to and decision-making over production resources and services by women in the banana seed systems is vital for equitable outcomes. Disease pressure on banana production experienced in southern Cameroon may influence gendered access to resources upsetting resource access equity. In theoretical terms, the study reveals dimensions of gender linked differences in resource control even where participation was evident. Thus, it indicates the need for in-depth understanding of power and social relations within households and the communities. This study reveals the nexus of disease challenge and resource access in banana systems. The study will be of interest to development practitioners, researchers and extension agents.